Shear response of RC beams encompassing hybrid CFRP strips and steel stirrups: Beam depth effect. (April 2022) - Alhassan, Mohammad A.; Al-Rousan, Rajai Z.; Alomari, Ibrahim S.; Amaireh, Layla
Abstract: In this study, nonlinear finite element analysis (FEA) was conducted to investigate the shear behavior of reinforced concrete (RC) beams encompassing hybrid CFRP strips and steel stirrups. Primal FEA models were calibrated and verified by comparing the load–deflection response, cracking, and failure modes with the experimentally tested RC beams. A parametric case study was then implemented to evaluate the influence of critical parameters including: configurations of CFRP strips (strip width, orientation angle), size effect, and concrete compressive strength. The results showed that changing the individual CFRP strip width while maintaining a constant total width has no significant effect on the behavior of the RC beams. Increasing the concrete compressive strength improves the bond strength between the CFRP strips and concrete leading to higher load capacity. Changing the orientation angle of the CFRP strips up to 45° has minor effect on the RC beam shear capacity. The contribution of the CFRP strips was more pronounced as the beam depth increased. A comparison showed that internally-integrated CFRP strips leads to better enhancement in the shear strength of RC beams than externally strengthening with CFRP composites.